Factors that influence the interest of youths in agricultural entrepreneurship - Abdul Aziz, Abdullah; Norhlilmatun Naem, Sulaiman (2013)
For as long as one can remember, agriculture has been considered a backwater sector. Hence it was not viewed as an attractive alternative to other work sectors such as manufacturing, private, and public sector employment. Nonetheless, the transformation of agriculture sector spearheaded by the Prime Minister of Malaysia has somewhat nullified the said perception. The primary purpose of this research is to identify the factors that influence youth interest to become agricultural entrepreneur, and to investigate the relationships of factors with the interest of youth to become entrepreneur. In this context, two hundred and fifty (250) youth in Pahang, Malaysia was selected as respondents from the population of agricultural entrepreneur in Malaysia. This study used two methods namely qualitative and quantitative as the best way to address the issue of agriculture entrepreneurship. In the qualitative method purposive sampling where chosen as data collection method. The respondents selected are those who have experience, expertise and involved for many years in the agricultural business. The first finding is that all respondent agrees that attitude, acceptance and knowledge are the factors that influence youth to become agriculture entrepreneurs. The second finding indicates that attitude and acceptances are the factors which significantly influence the youth interest in agriculture entrepreneurship. This study also surprisingly reveals that knowledge factor is not significant in influencing interest of youth to become entrepreneurs. Further, the open-ended questions reveals other factors which influenced young people to become entrepreneurs are; family support, government support and promotion through carnivals and festivals. These findings provide insight to the government officials in the ministry of agriculture to resolve unemployment issues and achieve successful economic growth through the agriculture sector.